Analyzing the teaching profile and competency-based training in online education: a case study of Ecuadorian professors - Castro Castillo, Graciela.; Cárdenas Cobo, Jesennia.; Tenutto Soldevilla, Marta.; Vidal Silva, Cristian. (Frontiers Media, 2024)
In the global landscape of education, the online modality has emerged as indispensable for extending access to academic training. This study delves into the teaching profile and competency-based training in online education within the context of Ecuador, a developing nation in South America. Employing a qualitative and exploratory approach, an exhaustive documentary review was conducted, followed by a comparative analysis of gathered information. The documentary review encompassed a meticulous examination of academic literature, governmental policies, and curricula pertaining to online education in Ecuador, with emphasis on selecting pertinent and representative sources. Through the comparative analysis, discernible patterns, similarities, differences, and trends regarding the teaching profile and competency-based training in Ecuadorian online education were identified. The findings present a comprehensive portrayal of how these dimensions have been addressed within Ecuador, thereby serving as a benchmark for future research endeavors. Moreover, they contribute to the advancement and enhancement of online academic programs not only within Ecuador but also in analogous contexts globally. Furthermore, the results offer valuable retrospective insights into the evolution of online education in Ecuador, shedding light on areas of strength and opportunities for refinement within this educational paradigm.
Keywords: Academic training; Online education; Teaching perspective; Teaching profile; Training by competencies